2020
DOI: 10.20524/aog.2020.0450
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of incidence and mortality in Asian-Americans with pancreatic adenocarcinoma: an epidemiological study

Abstract: Background Pancreatic cancer is the fourth most common cause of cancer-related deaths in the United States, with an estimated 45,750 deaths in 2019. Mortality outcomes seem to differ based on the ethnicity of the patients, with most studies focusing on the mortality and survival of Caucasians and African Americans. Little attention has been given, however, to Asian-American patients diagnosed with pancreatic adenocarcinoma (PAC). In this study, we aimed to investigate mortality rates in Asian-American patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…[ 31 ] Although obesity rates are lower in Asians in comparison with other ethnic groups in the US, it has also become an epidemic. [ 32 ] The age-adjusted prevalence of obesity in non-Hispanic Black and Hispanics in RI was 49% and 44%, respectively, which is similar to national estimates. [ 2 ] Within these two groups, women were more likely have obesity when compared to men.…”
Section: Discussionsupporting
confidence: 64%
“…[ 31 ] Although obesity rates are lower in Asians in comparison with other ethnic groups in the US, it has also become an epidemic. [ 32 ] The age-adjusted prevalence of obesity in non-Hispanic Black and Hispanics in RI was 49% and 44%, respectively, which is similar to national estimates. [ 2 ] Within these two groups, women were more likely have obesity when compared to men.…”
Section: Discussionsupporting
confidence: 64%
“…Asian cancer patients usually have a better prognosis when compared to Caucasians, whereas Afro-Americans have the worst evolution. [ 18 ] Due to the limited sample size, we did not further analyze the differences of prognosis among different sub-ethnic groups. Perhaps as the sample size further increases, we can analyze it in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that race disparities commonly exist in incidence, progression, pathological classification, and prognosis of gastrointestinal tumors. [ 31 , 32 ] This phenomenon also occurs in gastric cancer and esophageal cancer. [ 33 36 ] Gu et al also found that gene expression levels in gastric cancer vary with race [ 37 ] in his studies.…”
Section: Discussionmentioning
confidence: 99%